HARAPAN SUKU TALANG MAMAK TERHADAP PELAYANAN PENDIDIKAN DI DESA TALANG JERINJING KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Irfania, Roza Irfania; Natuna, Daeng Ayub Natuna Ayub; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Every people certainly have to hope for something. Similarly for Talang Mamak tribe in Talang Jerinjing village, sub distric Rengat Barat, district of Indragiri Hulu. They have expectations for a better educational services. To be able to compete in the global era as now, education is very important. The Talang Mamak tribe is one of the tribe or society that secluded, nomaden, and live in groups at forest.Â  So to gain access for formal education is difficult to get. This study aims to find out the expectations of society Talang Mamak tribe of educational services in Talang Jerinjing village, sub distric Rengat Barat, district of Indragiri Hulu. Based on the analysis performed with the data obtained from the observation method of data collection, data collection with interviews, data collection techniques to document, and triangulation of data collection techniques then take the conclusion, that most of the Talang Mamak tribe in the Talang Jerinjing village are hope the education service in the village can make them able to compete to toher in the era of technology information today. The people of Talang Mamak tribe in the Talang Jerinjing village also hopes the education service will make them to be recognized, just like any other community. Keywords : Hope, Talang Mamak Tribe, Education.